Investigation of changes in bone density and chemical composition associated with bone marrow oedema-type appearances in magnetic resonance images of the equine forelimb - Christine J. Heales (BMC Musculoskeletal Disorders, 2019)
Abstract Background The aetiology of bone marrow oedema-like abnormalities (BMOA) seen on magnetic resonance imaging (MRI) is as yet not fully understood. The current study aimed to investigate the potential of projection radiography and Raman microspectroscopy to provide information regarding the underlying physiological changes associated with BMOA in equine bone samples. Methods MRI was used to assess 65 limbs from 43 horses. A subset of 13 limbs provided 25 samples, 8 with BMOA present and 17 as controls; these were examined with projection radiography to assess bone mineral density and Raman spectroscopy to assess bone composition. Statistical analysis was conducted using SPSS, the relationship between BMOA and age was tested using binary logistic regression, other outcome measures via unpaired t-tests. Results Overall BMOA was found to be associated with locally increased bone density (p = 0.011), suggesting increased bone formation; however, no measurable changes relating to bone remodelling were found, and there were no detectable changes in the chemical composition of bone. Conclusions BMOA is associated with locally increased bone density, without an associated change in the chemical composition of bone, suggesting this is not linked to BMOA. The presence of increased bone density associated with BMOA does appear to suggest that an increased amount of bone formation is occurring in these regions, but as Raman microspectroscopy data do not demonstrate any significant changes in bone chemical composition associated with BMOA, it would appear that the increased bone volume is due to a greater amount of bone being formed rather than an imbalance in relation to bone remodelling. The study provides a proof of principle for the use of Raman microspectroscopy and projection radiography in in vitro studies of BMOA.